A construção da argumentação em produções textuais de alunos do 9º ano do Ensino Fundamental - Carvalho, Luiza Emanuele Monteiro de (2021)
Argumentation is inherent to human beings and make part of the whole communicative process in their social interactions. This fact help to understand why bring argumentation to the classroom as a necessary competence is so important, it is include in the Education’s Guide documentation, such as the National Curricular Base (BNCC), 2017, and the Referential’s Curriculum Documentation of Ceará (DCRC), 2019, as well to think about the role of the municipal network of Fortaleza which has directed effort to the entry to the Federal Institutes of Ceará through the selection processes, in recent years, that has proved to be essential for the insertion of its students in these educational institutions. This project began from the observation for many years of 9th grade classes and the students' difficulties in producing argumentative texts. As a result, the theoretical foundation and study of this research is based on argumentation from the perspective of Bakhtin (1979, 2003), Koch and Elias (2018), Koch (2011; 2015), Perelman and Tyteca (2014), Fiorin (2018) and many other linguists who have proposed the study of this object. In this perspective, it is considered essential to work with the construction of argumentation, into the classroom, through workshops, that it will be be separated into three blocks, which will use strategies based on Koch and Elias (2018), and on active methodologies, which promote the students’ autonomy and protagonism, in our research the 9th grade classes. As a result in the argumentative strategies the structure of argumentation is worked based on Koche, Marinello and Boff (2014), Koch and Elias (2018) and the DCRC (2019). It is hoped that the proposed activities can develop criticality, the reflection about the world where students are inserted and, in addition, to favoring knowledge about the elements that are parts of the opinion article’ genre which enables the students produce with property their own article, with the help the workshops presented during the Portuguese Language’ classes.